2016
DOI: 10.1080/21655979.2015.1134066
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of bacteriophage for controlling foaming in wastewater treatment plant- an eco-friendly approach

Abstract: This addendum to "Novel application of bacteriophage for controlling foaming in wastewater treatment plant-an eco-friendly approach " includes characteristics of the phages NOC1, NOC2 and NOC3 not discussed in the previous paper. The phage adsorption and host interaction properties, their sensitivity to pH and temperature are inferred. NOC2 is seen to be more temperature resistant while others are not. All the phages show pH sensitivity. There is a variance observed in the behavior of these phages. Also, appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Khainar et al isolated specific bacteriophages against nocardioforms on active sludge process. The activity of three phages applied in a cocktail at the lab scale reactor reduced foam formation [104]. Choi et al isolated a bacteriophage from sewage infecting Sphaerotilus natans, known to cause filamentous bulking in wastewater treatment systems, and their results showed that phage application diminished the sludge volume index and turbidity of the supernatant, indicating that phages can be used in this concern too [105].…”
Section: Bacteriophages In Bioremediationmentioning
confidence: 99%
“…Khainar et al isolated specific bacteriophages against nocardioforms on active sludge process. The activity of three phages applied in a cocktail at the lab scale reactor reduced foam formation [104]. Choi et al isolated a bacteriophage from sewage infecting Sphaerotilus natans, known to cause filamentous bulking in wastewater treatment systems, and their results showed that phage application diminished the sludge volume index and turbidity of the supernatant, indicating that phages can be used in this concern too [105].…”
Section: Bacteriophages In Bioremediationmentioning
confidence: 99%
“…Phage-mediated mortality has the potential to influence the treatment performance of a system through controlling the abundance of key functional groups, leading to their utilisation as a biocontrol strategy to lyse filamentous bacteria that are responsible for bulking in activated sludge [ 16 , 17 ]. In contrast, bacteriophage predation in wastewater systems has been demonstrated to cause the collapse of reactors [ 18 ] and the failure of bacterial biological processes such as phosphorus removal and nitrification [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages are highly abundant in engineered wastewater systems, appear to be active components of activated sludge systems and are able to infect both planktonic and bio lm associated bacterial cells [13][14][15]. Phage-mediated mortality has the potential to in uence the treatment performance of a system through controlling the abundance of key functional groups, leading to their utilisation as a biocontrol strategy to lyse lamentous bacteria that are responsible for bulking in activated sludge [16,17]. In contrast, bacteriophage predation in wastewater systems has also resulted in failures of bacterial biological processes such as phosphorus removal and nitri cation [18,19].…”
Section: Introductionmentioning
confidence: 99%